Asiatic Acid Alleviates Renal Damage by Upregulating STBD1-Mediated Glycophagy in Diabetic Kidney Disease - Lei Guo; Peili Wu; Qijian Feng; Xiaochun Lin; Yuan Wang; Minghai Wu; Feifei Cai; Jin Zhang; Chuyi Yang; Xuelin Li; Churan Wen; Yingbei Lin; et al. (Biomedicines, 2025)
Background/Objectives: The role of glycogen metabolism in diabetic kidney disease (DKD) remains unclear. This study investigated the therapeutic potential of asiatic acid (AA) on glycogen metabolism in DKD and its underlying mechanisms. Methods: A DKD mouse model was established using a high-fat diet and streptozotocin, followed by AA treatment for 8 weeks. Network pharmacology and molecular docking identified STBD1 as a potential target of AA, and its overexpression in mice was performed. Results: AA reduced blood glucose levels and the urinary albumin-to-creatinine ratio (UACR) and downregulated TGFβ-1, KIM-1, and PDK4. Additionally, AA treatment reversed abnormal glycogen accumulation and restored STBD1 expression. Network pharmacology and molecular docking identified STBD1 as a potential target of AA, and its overexpression in mice demonstrated similar beneficial effects. Gene enrichment analysis revealed that STBD1 is involved in key metabolic pathways related to DKD. Conclusions: These findings suggest that AA alleviates renal damage in DKD, possibly through modulation of STBD1, highlighting its therapeutic potential and the critical role of STBD1 in renal glycophagy.